I shall return - Cagas, Cosme R. (Outskirts Press, 2013)
In the first dark days of 1942, Gen. MacArthur daringly escaped to Australia. He kept his promise to return when US troops stormed back into the Philippines in 1944. Last seen at the dreaded Death March, Junior's uncle also promised to return...but could he do so?